Comprehensive frequency regulation control strategy of thermal power generating unit and ESS considering flexible load simultaneously participating in AGC. (February 2023) - Li, Cuiping; Feng, Changsheng; Li, Junhui; Hu, Dacheng; Zhu, Xingxu
Abstract: The strategy for frequency modulation control of energy storage assisted AGC (automatic generation control) systems with flexible loads was looked into from the viewpoint of source charge interaction in order to optimize the problem of single cell storage with flexible loads on the load side with slower energy storage forces in less fluctuating grids. In order to take advantage of both system stability and energy storage safety, a battery energy storage system is configured on the power side, and a linear regression function model is used to characterize its maximum power constraint in different needs as well as different levels of charge. Upper and lower limits of the total controllable force were determined by simultaneously invoking flexible loads on the load side and polymerizing the material using a method under central control. In order to extend the useful life of energy storage while also solving the frequency problem more quickly and effectively, different regions are divided using the frequency deviation signal, which is regulated by various modes of action in various regions. Four frequency modulation scenarios with and without flexible loads and energy storage systems engaged in AGC frequency modulation were compared using MATLAB/SIMULINK for simulation validation. The findings demonstrated that the suggested control technique may improve frequency modulation performance and lower the lifetime loss of energy storage. Graphical abstract: Unlabelled Image Highlights: The method of using flexible load on the load side and energy storage on the power side to regulate frequency is proposed. The depth limit of energy storage action is proposed, which clarifies the dead zone and the maximum output limit. The operation conditions of energy storage and flexible load are defined, and different operation states of them are divided.